Preferential solvation and ion association properties in aqueous dimethyl sulfoxide solutions. Issue 45 (8th November 2016) - Krishnamoorthy, Anand Narayanan; Zeman, Johannes; Holm, Christian; Smiatek, Jens
Abstract : We study the solvation and association mechanism of an ion pair in aqueous DMSO solution. Our results verify a homoselective solvation behavior which can be related to strong non-ideal solution properties. Abstract : We study the solvation and the association properties of ion pairs in aqueous dimethyl sulfoxide (DMSO) solution by atomistic molecular dynamics (MD) simulations. The ion pair is composed of two lithium and a single sulfonated diphenyl sulfone ion whose properties are studied under the influence of different DMSO concentrations. For increasing mole fractions of DMSO, we observe a non-ideal behavior of the solution as indicated by the derivatives of the chemical activity. Our findings are complemented by dielectric spectra, which also verify a complex DMSO–water mixing behavior. In agreement with these results, further simulation outcomes reveal an aqueous homoselective solvation of the ion species which fosters the occurrence of pronounced ion association constants at higher DMSO mole fractions. The consequences of this finding are demonstrated by lower ionic conductivities for increasing concentrations of DMSO.